Variability and spatial fine structure of precipitating and trapped medium‐energy electron fluxes in the noon sector. Issue 2 (27th February 2014) - Hargreaves, J. K.; Birch, M. J.; Evans, D. S.
<x xml:space="preserve">Abstract</x> The relationships between the precipitating and trapped components of magnetospheric electron flux for energy ranges exceeding 30 and 100 keV have been investigated using data from polar orbiting satellites, the study being restricted to a limited geographic region at auroral latitudes in the noon sector. The electron flux of these energies is the cause of auroral radio absorption. The data are analyzed at two levels of detail. Variations between different passes are studied using their median values, and variations within passes are derived from individual data points at 2 s intervals, equivalent to about 10 km in distance. Several types of behavior are recognized. Basically, the ratio of precipitating to trapped flux at energies exceeding 30 keV varies in proportion to the trapped flux, though there is a limiting upper value where the two components are approximately equal. The precipitating flux never exceeds the trapped flux by any significant amount. These types appear to be consistent with weak and strong pitch angle scatterings, respectively. The precipitation at >100 keV varies somewhat with the >100 keV trapped flux but more strongly with the >30 keV component, consistent with scattering by chorus waves produced by electrons less energetic than those being scattered. Comparison between the two energy ranges shows that the precipitating component is always softer than the trapped. The detailed relationship between the precipitating and trapped components varies from pass to pass by an amount related to the east‐west component of the interplanetary magnetic field. Superimposed on the above behavior are large reductions of precipitation, spatial rather than temporal in nature, during which the trapped flux remains virtually unchanged. These reductions appear to be due to structures some tens of kilometers across, perhaps related to "ducts" within the magnetosphere. Some theoretical considerations based on the Kennel and Petscheck theory of scattering are given in an Appendix.